Wake-flow-induced vibrations of vertical hangers behind the tower of a long-span suspension bridge. (15th August 2018) - Chen, Wenli; Gao, Donglai; Li, Hui; Hu, Hui
Highlights: The wake-flow-induced vibrations of vertical hangers behind the tower of a suspension bridge is reproduced in a wind tunnel. Regular vortex shedding from the tower column model is with a Strouhal number ( St ) of 0.20 and the turbulence intensity of wake flow is found quite high. The vibration frequencies of the vertical cables are synchronized with the vortex shedding from the upstream tower within a certain velocity range, during which severe cable vibrations take place. When the incoming wind speed becomes high, the cable vibrations exhibit multi-mode characteristics. Abstract: Violent vibrations have been reported in the vertical hangers of long-span suspension bridges, especially for those located in the vicinity of the towers. In the present study, an experimental investigation is performed to characterize the wake-flow-induced vibrations of vertical hangers behind the tower of a suspension bridge. The tower column and vertical cable models are determined by using a long-span suspension bridge with a geometrical scale ratio of 1:10. Regular vortex shedding from the tower column model is detected in the near wake with a Strouhal number ( St ) of 0.20, and the turbulence intensity of the wake flow behind the tower column model is found to be quite high. Arranged at different stations behind the tower column model, the vertical cables experience violent vibrations. The vibration frequencies of the vertical cables are synchronized with the vortex shedding from the upstream tower model within a certain velocity range, during which severe cable vibrations take place. When the incoming wind speed becomes high, the cable vibrations exhibit multimode characteristics. It is also found that the vertical cables arranged at the rear are subject to the combined interferences of the tower column model and the front cables. As a result, the vibration responses of the rear cables are more violent than those of the front cables.